Design and Implementation of Voltage Source Inverter using PWM Technique - Doranga, Saroj; Nepal, Rajeev; Timsina, Pratigya (Scientific Researches in Academia, 2023)
With increasing demand for electricity and diminishing conventional energy resources, there is a pressing need for alternative energy sources. This project aims to construct a Power Inverter that can serve as a reliable power source for heavy equipment. The Voltage Source Inverter (VSI) is a power electronic device that converts DC power to AC power at the required output voltage and frequency level. A two-level inverter produces an output voltage source or current with levels of 0 or positive or negative volts DC. A variable voltage Pulse Width Modulation (PWM) inverter produces a near sinusoidal voltage from several levels of DC voltages, with minimum harmonic distortion and variable output voltage. Using MOSFETs and a microcontroller, this project developed a hardware model for a PWM H-Bridge inverter. A potentiometer serves as a tuner to adjust the duration of the gate signals for driving the MOSFETs, which changes the width of the output voltages, thereby achieving pulse width modulation. PROTEUS simulation models were designed to validate the inverter's performance. The proposed project's objective is to design and implement a Voltage Source Inverter using PWM technique.